THE INFLUENCE OF COMPETITIVE PRICE, QUALITY OF SERVICE AND PRODUCT QUALITY ON CUSTOMER SATISFACTION (STUDY OF MARKETING MANAGEMENT LITERTURE) - Prihartono, Prihartono (Dinasti International Journal of Digital Business Management, 2021)
The Literature Review article on the Effect of Competitive Price, Service Quality and Product Quality on Customer Satisfaction is a scientific article that aims to build a research hypothesis on the influence between variables that will be used in further research, within the scope of Marketing Management. The method of writing this Literture Review article is using the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this study are: 1) Competitive Price has an effect on Customer Satisfaction; 2) Service Quality has an effect on Customer Satisfaction; and 3) Product Quality has an effect on Customer Satisfaction. Apart from these 3 exogenous variables that affect the endogenous variable Customer Satisfaction, there are many other factors including employee knowledge, polite employees, efficiency and on time delivery.